Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Discover comprehensive solutions to your questions from a wide network of experts on our user-friendly platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To determine [tex]\((f - g)(-3)\)[/tex], we need to follow a detailed, step-by-step process.
First, let's define the functions [tex]\(f(x)\)[/tex] and [tex]\(g(x)\)[/tex]:
[tex]\[ f(x) = 3x^2 + 6 \][/tex]
[tex]\[ g(x) = -5x + 2 \][/tex]
We need to find the value of [tex]\((f - g)(-3)\)[/tex]. This means we will evaluate both [tex]\(f(x)\)[/tex] and [tex]\(g(x)\)[/tex] at [tex]\(x = -3\)[/tex], and then find the difference between these values.
1. Evaluate [tex]\(f(-3)\)[/tex]:
Substitute [tex]\(x = -3\)[/tex] into the function [tex]\(f(x)\)[/tex]:
[tex]\[ f(-3) = 3(-3)^2 + 6 \][/tex]
Calculate [tex]\((-3)^2\)[/tex]:
[tex]\[ (-3)^2 = 9 \][/tex]
Now, multiply by 3:
[tex]\[ 3 \cdot 9 = 27 \][/tex]
Add 6:
[tex]\[ 27 + 6 = 33 \][/tex]
Therefore:
[tex]\[ f(-3) = 33 \][/tex]
2. Evaluate [tex]\(g(-3)\)[/tex]:
Substitute [tex]\(x = -3\)[/tex] into the function [tex]\(g(x)\)[/tex]:
[tex]\[ g(-3) = -5(-3) + 2 \][/tex]
Calculate [tex]\(-5 \cdot -3\)[/tex]:
[tex]\[ -5 \cdot -3 = 15 \][/tex]
Add 2:
[tex]\[ 15 + 2 = 17 \][/tex]
Therefore:
[tex]\[ g(-3) = 17 \][/tex]
3. Calculate [tex]\((f - g)(-3)\)[/tex]:
Subtract [tex]\(g(-3)\)[/tex] from [tex]\(f(-3)\)[/tex]:
[tex]\[ (f - g)(-3) = f(-3) - g(-3) \][/tex]
Substitute the values we found:
[tex]\[ (f - g)(-3) = 33 - 17 \][/tex]
Perform the subtraction:
[tex]\[ 33 - 17 = 16 \][/tex]
Thus:
[tex]\[ (f - g)(-3) = 16 \][/tex]
First, let's define the functions [tex]\(f(x)\)[/tex] and [tex]\(g(x)\)[/tex]:
[tex]\[ f(x) = 3x^2 + 6 \][/tex]
[tex]\[ g(x) = -5x + 2 \][/tex]
We need to find the value of [tex]\((f - g)(-3)\)[/tex]. This means we will evaluate both [tex]\(f(x)\)[/tex] and [tex]\(g(x)\)[/tex] at [tex]\(x = -3\)[/tex], and then find the difference between these values.
1. Evaluate [tex]\(f(-3)\)[/tex]:
Substitute [tex]\(x = -3\)[/tex] into the function [tex]\(f(x)\)[/tex]:
[tex]\[ f(-3) = 3(-3)^2 + 6 \][/tex]
Calculate [tex]\((-3)^2\)[/tex]:
[tex]\[ (-3)^2 = 9 \][/tex]
Now, multiply by 3:
[tex]\[ 3 \cdot 9 = 27 \][/tex]
Add 6:
[tex]\[ 27 + 6 = 33 \][/tex]
Therefore:
[tex]\[ f(-3) = 33 \][/tex]
2. Evaluate [tex]\(g(-3)\)[/tex]:
Substitute [tex]\(x = -3\)[/tex] into the function [tex]\(g(x)\)[/tex]:
[tex]\[ g(-3) = -5(-3) + 2 \][/tex]
Calculate [tex]\(-5 \cdot -3\)[/tex]:
[tex]\[ -5 \cdot -3 = 15 \][/tex]
Add 2:
[tex]\[ 15 + 2 = 17 \][/tex]
Therefore:
[tex]\[ g(-3) = 17 \][/tex]
3. Calculate [tex]\((f - g)(-3)\)[/tex]:
Subtract [tex]\(g(-3)\)[/tex] from [tex]\(f(-3)\)[/tex]:
[tex]\[ (f - g)(-3) = f(-3) - g(-3) \][/tex]
Substitute the values we found:
[tex]\[ (f - g)(-3) = 33 - 17 \][/tex]
Perform the subtraction:
[tex]\[ 33 - 17 = 16 \][/tex]
Thus:
[tex]\[ (f - g)(-3) = 16 \][/tex]
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.